Credit ratings and structured finance - Jens Josephson; Joel Andrew Shapiro (Research Institute of Industrial Economics (IFN), 2018)
The poor performance of credit ratings of structured finance products in the financial crisis has prompted investigation into the role of credit rating agencies (CRAs) in designing and marketing these products. We analyze a two-period reputation model in which a CRA both designs and rates securities that are sold both to investors who require highly rated securities and investors who are unconstrained. Assets are pooled and senior and junior tranches are issued with a waterfall structure. When rating standards are low, the CRA will include only risky assets in the securitization pool, serving both types of investors without any rating inflation. Rating inflation may be non-monotonic in rating standards, with no rating inflation when rating standards are low and high.
Keywords: G24; L14; 330; Credit rating agencies; Reputation; Structured finance